HUBUNGAN PENGETAHUAN, TINGKAT PENDIDIKAN, DAN PERSEPSI MASYARAKAT PADA PETUGAS KESEHATAN TERHADAP PENCEGAHAN DBD DI WILAYAH KERJA PUSKESMAS BAROS - Azhar Febriansyah, Muhammad; Mulyadi, Egi; Tarwati, Kartika (Lafadz Jaya Publisher, 2023)
Until now, DHF is one of the communicable diseases which is a major public health problem in all tropical and subtropical regions of the world including the islands of Indonesia to northern Australia. DHF is a disease caused by one of four different dengue viruses and is transmitted by mosquitoes, especially Aedes aegypti. This study aims to determine the relationship between knowledge, level of education and public perception of health workers on DHF prevention in the working area of the Baros Health Center. This research method uses descriptive analytic with cross sectional approach. The number of respondents in this study were 92 respondents. The instrument in the research is a questionnaire. The research was analyzed using the Chi square formula. Statistical test results of the relationship between knowledge of DHF prevention and chi-square at the resulting P value of 0.000 <0.05. Statistical test results of the relationship between education level and DHF prevention with chi-square resulting P value of 0.000 <0.05, and Statistical test of the relationship between public perception of health workers on DHF prevention with a chi-square P value of 0.015 <0.05. The conclusion is that there is a relationship between knowledge and prevention of DHF in the Working Area of the Baros Health Center, there is a relationship between education level and prevention of DHF in the Working Area of the Baros Health Center, and there is a relationship between the public's perception of health workers towards the prevention of DHF in the Working Area of the Baros Health Center. It is recommended for the Baros Community Health Center to further improve and optimize counseling or outreach activities regarding DHF and how to prevent DHF.